Encumbered by vulnerability and temporality – the meanings of trigger situations when learning to live with diabetes. Issue 19 (1st August 2016) - Kneck, Åsa; Eriksson, Lars E; Lundman, Berit; Fagerberg, Ingegerd
Abstract : Aims and objectives: The aim of the study was to illuminate the meanings of trigger situations experienced in everyday life when learning to live with diabetes. Background: Adults become active learners when faced with situations they do not know how to manage, triggering a need to understand something in a different way than before. Knowing more about experiential learning for persons living with diabetes is important for understanding how learning can be supported by health care. Design: A life‐world approach with a phenomenological hermeneutical method, inspired by the philosophy of Paul Ricoeur. Methods: This method was used for interpreting transcriptions of interviews and consists of three stages: naïve understanding, structural analysis and a comprehensive understanding. Participants ( n  = 13), with either type I or type II diabetes, were interviewed on three different occasions over a three‐year period after being diagnosed with diabetes. Results: When learning to live with diabetes, the meanings of trigger situations were described as 'the unpredictable body heightens insecurity with awareness of one's own dependability', 'losing control in unsustainable situations' and 'encumbered by vulnerability and temporality in earlier familiar situations'. Conclusion: The meanings of trigger situations were to lose the smooth, unreflected way of managing an everyday life situation, interlaced with feelings of lost control of how to live with new insights of being vulnerable. Trigger situations meant an opportunity for learning, as well as being demanding, unplanned and with limited freedom of choice. Trigger situations presented life and body as unpredictable. Relevance to clinical practice: If healthcare professionals can identify the worries and questions raised in trigger situations, knowledge gaps can be identified and reflected on to stimulate learning.